2005
DOI: 10.1111/j.1420-9101.2005.00937.x
|View full text |Cite
|
Sign up to set email alerts
|

Pollinating fig waSPS: genetic consequences of island recolonization

Abstract: The levels of genetic diversity and gene flow may influence the long‐term persistence of populations. Using microsatellite markers, we investigated genetic diversity and genetic differentiation in island (Krakatau archipelago, Indonesia) and mainland (Java and Sumatra, Indonesia) populations of Liporrhopalum tentacularis and Ceratosolen bisulcatus, the fig wasp pollinators of two dioecious Ficus (fig tree) species. Genetic diversity in Krakatau archipelago populations was similar to that found on the mainland.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
73
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(79 citation statements)
references
References 49 publications
6
73
0
Order By: Relevance
“…crops (33, 34). Pollen dispersal ranges of 1 to 2 km have been inferred for the dioecious F. pumila in China (35), but genetic studies of two pollinators of dioecious fig trees from Indonesia nonetheless found low levels of population subdivision between mainland and island populations over 40 km apart (15), suggesting that the nature of the breeding system is a weak predictor of gene-flow distances in fig trees. How does C. arabicus manage to pollinate F. sycomorus trees over 100 km apart? The slow flight speed of fig wasps (36) precludes active, directed flight in the time available during a 48-h adult lifespan.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…crops (33, 34). Pollen dispersal ranges of 1 to 2 km have been inferred for the dioecious F. pumila in China (35), but genetic studies of two pollinators of dioecious fig trees from Indonesia nonetheless found low levels of population subdivision between mainland and island populations over 40 km apart (15), suggesting that the nature of the breeding system is a weak predictor of gene-flow distances in fig trees. How does C. arabicus manage to pollinate F. sycomorus trees over 100 km apart? The slow flight speed of fig wasps (36) precludes active, directed flight in the time available during a 48-h adult lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…Pollen dispersal distances for some species have been found to range from hundreds of meters (5)(6)(7)(8)(9)(10)(11) to kilometers (12,13). Long-distance pollen flow between fig trees (Ficus spp., Moraceae) is particularly well documented (14,15). Each of the 800 or so species of fig tree is pollinated exclusively by one or a few host-specific fig wasps (Agaonidae) (16) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Each fig species is exclusively pollinated by one or a small number of species of host-plant-specific fig wasps (Agaonidae) that enter the trees' globular inflorescences (figs) in order to lay their eggs [23]. Pollinating fig wasps are short-lived, weak-flying insects, but paternity analyses and population structuring of their host populations suggest that whereas some species disperse locally [24], others disperse across much longer distances [8,13,25], initially using fast-flowing air to transport them passively in whichever direction it is moving [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Different host species appear to produce different blends that the associated wasps recognize. Genetic work has shown that the pollen-bearing wasps routinely disperse many kilometers, with the result that the areas covered by effective breeding populations of figs are often on the order of a hundred or more square kilometers, an order of magnitude larger than that documented for any other plant species (Nason et al 1998; also see Compton 1990see Compton , 1993Harrison & Rasplus 2006;Ware & Compton 1992;Zavodna et al 2005). Interestingly, high ratios of anthers to female flowers and produce much more pollen per syconium than do actively pollinated figs, and their mature anthers tend to dehisce naturally, facilitating the passive collection of pollen by their pollinators (pollen adheres to various parts of the body surface) (Jousselin et al 2003a.…”
Section: Natural History Of the Fig And Pollinator Wasp (And Associates)mentioning
confidence: 99%